The effect of Suggestopedia method on Indonesian EFL learners’ reading achievement - Langgeng Budianto; Rendhi Fatrisna Yuniar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research is intended at investigating the effect of suggestopedia method on Indonesian EFL learners’ reading achievement in descriptive texts. Suggestopedia method in this research described as the use of classic music as the background in the process of teaching and learning. This research used Quasiexperimental research design and involving two classes of SMP Al Izzah IIBS, Batu. There were 30 students as the experimental group and 27 students as control group. The participants were given treatment of suggestopedia in 3 meetings (each meeting lasted for 90 minutes). They were given two kinds of tests as the instrument in this study, namely pre-test and post-test. The result of the pre-test and post-test was analyzed by using t-test in SPSS. The research revealed that there was a significant progress between the pre-testand the post-test score.